2020
DOI: 10.1101/2020.04.09.20058966
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of Early HIV-1 Infection among Febrile Persons and Blood Donors in Oyo State, Nigeria

Abstract: About 37.9 million persons are infected with HIV globally resulting in 770,000 deaths. Over 50% of this infection and deaths occur in Sub-Saharan Africa with countries like Nigeria greatly affected. The country also has one of the highest rates of new infections globally. Diverse HIV-1 subtypes have been identified in the country. Febrile persons and blood donors pose a great transmission risk in the country especially during the early stages of infection. HIV-1 rapid kits are routinely used for diagnosis amon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Analysis of this concept would further situate the impact of molecular strains of HIV-1 on residual risk. Some studies have shown that viral load and serology (Antibodies and P2 antigens) were essential in interpreting data evaluating the effectiveness of the donation security system put in place to reduce the risk of HIV transmission in transfusion [1,[49][50][51][52]. The number of times each concept appears shows its importance in the various full articles included in the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of this concept would further situate the impact of molecular strains of HIV-1 on residual risk. Some studies have shown that viral load and serology (Antibodies and P2 antigens) were essential in interpreting data evaluating the effectiveness of the donation security system put in place to reduce the risk of HIV transmission in transfusion [1,[49][50][51][52]. The number of times each concept appears shows its importance in the various full articles included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the most recent data from the World Health Organization (WHO) still show that there are annually nearly 2 million new people infected with HIV and with 36.9 million people living with this chronic infection. in 2020 [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These resource-limited countries are faced with this problem because they are still unable to obtain techniques based on nucleic acid research, but also because of low coverage of 4th generation screening tests (Ab/Ag, p24) in blood banks [5]. Without forgetting also the lack of information on rapid screening tests used by almost all blood banks in these countries of Sub-Saharan Africa for the screening of TTIs thus promoting a high risk of transmission of TTIs [6][7].…”
Section: Introductionmentioning
confidence: 99%